Designing an E-Commerce System for Local Products with Web-Based Map Integration Using The Laravel Framework - AL Fazri; Rina Novita; Amrizal; Agus Nur Khomarudin; Rabby Nazly (Universitas Islam Kuantan Singingi, 2025)
The development of information and communication technology has opened up new opportunities in promoting and marketing local products and tourist destinations. However, there are still many obstacles faced by local businesses, such as limited market access, lack of promotion, and the absence of marketing system integration. This research aims to design and implement a Harau local product e-commerce system with map integration on a Laravel-based web application. This platform is designed to facilitate the sale of local products while providing navigation of store locations through interactive maps. The system development method uses Agile methodology with Laravel framework and MVC architecture. The system successfully integrates role-based authentication features, product management, conventional payment systems, and digital mapping using Google Maps API and Leaflet Maps through the Laraflet plugin. The test results show a system validity rate of 75% based on expert assessment and an effectiveness rate of 80.33% based on user surveys. The system has met good quality standards with all main features functioning according to the black-box testing results. This platform makes a significant contribution to the empowerment of local MSMEs by providing innovative solutions to overcome location problems that have been the main obstacles for local businesses.